Erythromycin Suppresses the Cigarette Smoke Extract-Exposed Dendritic Cell-Mediated Polarization of CD4+ T Cells into Th17 Cells. (21st January 2020) - Liu, Jifeng; Zhong, Xiaoning; He, Zhiyi; Zhang, Jianquan; Bai, Jing; Liu, Guangnan; Liang, Yi; Ya, Leilei; Qin, Xianglin
Abstract : Cigarette smoke is a major effector of chronic obstructive pulmonary disease (COPD), and Th17 cells and dendritic cells (DCs) involve in the pathogenesis of COPD. Previous studies have demonstrated the anti-inflammatory effects of macrolides. However, the effects of macrolides on the cigarette smoke extract- (CSE-) induced immune response are unclear. Accordingly, in this study, we evaluated the effects of erythromycin (EM) on CSE-exposed DCs polarizing naïve CD4 + T cells into Th17 cells. DCs were generated from bone marrow-derived mononuclear cells isolated from male BALB/c mice and divided into five groups: control DC group, CSE-exposed DC group, CD40-antibody-blocked CSE-exposed DC group, and EM-treated CSE-exposed DC group. The function of polarizing CD4 + T cells into Th17 cells induced by all four groups of DCs was assayed based on the mixed lymphocyte reaction (MLR) of naïve CD4 + T cells. CD40 expression in DCs in the CSE-exposed group increased significantly compared with that in the control group (P < 0.05 ). The Th17 cells in the CSE-exposed DC/MLR group increased significantly compared with those in the control DC/MLR group (P < 0.05 ). Moreover, Th17 cells in the CD40-blocked CSE-exposed DC/MLR group and EM-treated CSE-exposed DC/MLR group were reduced compared with those in the CSE-exposed DC/MLR group (P < 0.05 ). Thus, these findings suggested that EM suppressed the CSE-exposed DC-mediated polarization of CD4 + T cells into Th17 cells and that this effect may be mediated through inhibition of the CD40/CD40L pathway.